On the non–periodic groups, whose subgroups of infinite special rank are transitively normal - Kurdachenko, L.A.; Subbotin, I.Ya.; Velychko, T.V. (Algebra and Discrete Mathematics, 2020)
This paper devoted to the non-periodic locally generalized radical groups, whose subgroups of infinite special rank are transitively normal. We proved that if such a group G includes an ascendant locally nilpotent subgroup of infinite special rank, then G is abelian.